Positional isomers of 2r-extended phenolate-based inverted solvatochromic dyes: Shifting the inversion point by relocating the aryl spacer - Aliaga-Vidal, C; Aliaga-Vidal, C; Dominguez-Caru, M (ELSEVIER SCI LTD, 2026)
Phenolate-nitroaryl dyes exhibit inverted solvatochromism that is highly sensitive to the architecture of the 2r-bridge. By reversing the sequence within the 2r-bridge of a phenolate-imine-aryl-nitroaryl framework and systematically varying phenylene or thienylene spacers and nitroaryl acceptors, we obtained dyes that preserve solvatochromic inversion behavior while shifting the solvatochromic inversion point SIP at lower solvent polarities with enhanced sensitivity in aprotic solvents. Multiparametric analysis shows that hydrogen bonding governs the negative branch of the inversion curve, whereas polarizability and dipolar interactions dominate the positive branch. TDDFT calculations confirm a phenolate-to-nitroaryl charge-transfer transition, modulated by the 2r-spacer. These results demonstrate that rational 2r-bridge engineering provides a powerful handle to tune both the polarity domain and the amplitude of solvatochromic inversion.